Biological Control of Streptomyces murinus against Colletotrichum causing Anthracnose Disease on Tomato Fruits - Hien Trang Nguyen; Thanh Long Le; Thy Dan Huyen Nguyen; Thi Thanh Tuyet Truong; Thi Thuy Tien Nguyen (Journal of Pure and Applied Microbiology)
Streptomyces is a genus recognized for combating many plant pathogens, including those affecting post-harvest fruits. This study aimed to identify the Colletotrichum fungus responsible for anthracnose in tomatoes and evaluate the antifungal efficacy of Streptomyces murinus NARZ. The Colletotrichum isolate was identified as C. scovillei C3 through morphological characteristics, ITS region sequencing, and phylogenetic analysis. Culture filtrates (CF) of S. murinus NARZ at concentrations from 0% to 50% (in 10% intervals) were tested for antifungal activity against C. scovillei C3. The Percentage Inhibition of Radial Growth, calculated using colony diameters, showed that a 30.40% CF concentration (EC50) inhibited 50% of C. scovillei C3 growth on PDA plates. The CF exhibited heat stability, with PIRG values ranging from 62.93% to 65.35% across temperatures of 30 °C to 90 °C. In vivo trials involved treating tomatoes with CF using pre-treatment (spraying 24 hours before inoculation) or post-treatment (spraying 24 hours after inoculation). After seven days, pre-treated tomatoes with 50% CF showed a disease incidence of 83.33%, while all other treatments had a 100% incidence. Lesion diameters in the 50% CF treatment were significantly smaller (p < 0.05) compared to lower CF concentrations and showed results similar to the Chlorothalonil treatment. Pre-treatment was more effective than post-treatment, with lesion diameters of 5.40 mm and 8.73 mm, respectively. PCR analysis confirmed that S. murinus NARZ produced antifungal compounds via PKS-I, PKS-II, and NRPS gene clusters. These findings suggest that S. murinus NARZ could be an effective alternative to chemical fungicides for managing tomato anthracnose caused by C. scovillei.